Polar Perspectives No 13 - The Intelligence Community Must Evolve To Meet the Reality of Arctic Change - Maddox, Marisol; Lea, Lyston (Woodrow Wilson International Center for Scholars, 2023)
Climate change is accelerating and significant changes are occurring at relatively low levels of warming. 1 The Arctic is warming faster than anywhere on Earth, with tremendous implications for U.S. homeland and national security, as well as U.S. security interests abroad. 2 Future conditions are not well-represented by past experiences so it is important for the U.S. intelligence community (IC) to evolve to meet the demands of this new reality. 3 This includes creating an holistic approach towards the Arctic region, as well as several other targeted, structural interventions pertaining to Arctic engagement and equities. This natural evolution will allow the IC to provide more robust, agile, and comprehensive support to policymakers and the military; properly reflecting the period of unprecedented complexity and consequence we are now within.